1999
DOI: 10.1002/(sici)1097-0215(19990719)82:2<161::aid-ijc2>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of childhood leukemia in Southern Ontario, Canada, and exposure to magnetic fields in residences

Abstract: A population‐based case‐control study was conducted in Ontario, Canada, to assess the relation between the risk of childhood leukemia and residential exposure to magnetic fields. Participating subjects consisted of 201 cases, diagnosed at 0 to 14 years of age during 1985–1993, ascertained from the records at the Hospital for Sick Children (Toronto), and 406 individually matched controls. Where possible, point‐in‐time measurements of magnetic fields were made in all residences occupied by subjects during the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 20 publications
(40 reference statements)
1
16
0
Order By: Relevance
“…A study from New Zealand (Dockerty et al, 1998) found no significant increase in risk using as exposure metrics the means of two 24-h measurements made in the centre of the most used room and by the child's bed. Two recent Canadian studies (McBride et al, 1999;Green et al, 1999) found no increase in risk using 48-h personal monitoring. The influence of the body on the electric field during personal monitoring, together with the possibility that case children may have changed their behaviour since developing the disease make these results hard to interpret.…”
Section: Discussionmentioning
confidence: 93%
“…A study from New Zealand (Dockerty et al, 1998) found no significant increase in risk using as exposure metrics the means of two 24-h measurements made in the centre of the most used room and by the child's bed. Two recent Canadian studies (McBride et al, 1999;Green et al, 1999) found no increase in risk using 48-h personal monitoring. The influence of the body on the electric field during personal monitoring, together with the possibility that case children may have changed their behaviour since developing the disease make these results hard to interpret.…”
Section: Discussionmentioning
confidence: 93%
“…Initial studies characterized field levels using short-term, or "spot," measurements taken immediately outside (23) or within residences (12), the latter obtained in the child's and parents' bedrooms. Subsequently, 24-hr measurements were obtained in rooms in which subjects spent a substantial proportion of time, based on interview data (9,15,19,21,(33)(34)(35)(36)(37). Such measurements are made after diagnosis, but unlike measurements based only on power lines, these inhome measurements reflect all sources of magnetic fields in the residence (38).…”
Section: Residentialmentioning
confidence: 99%
“…In residential studies assessing exposure using spot and/or 24-hr or longer area magnetic field measurements, increases in leukemia, ranging from 1.3-to 1.5-fold elevated, were reported for children with average magnetic field exposures ≥0.2 µT in Denver (based on 3 cases) (12), Los Angeles (based on 20 cases with exposures ≥0.268 µT) (15), Lower Saxony and Berlin, Germany (based on 4 cases) (33,34), nine Midwestern and mid-Atlantic states in the United States (based on 58 cases) (21), five provinces in Canada (based on 54 cases) (9), and the United Kingdom (based on 21 cases) (including England, Wales, and Scotland) (37). A 3.3-fold increase (95% confidence interval [CI] = 0.5-23.7) of leukemia was linked with 24-hr children's bedroom timeweighted average measurements ≥0.2 µT in a study in New Zealand (based on 5 cases) (34,79), and an odds ratio of 1.1 (95% CI = 0.31-4.06) was linked with point-in-time measurements ≥0.13 µT taken in the child's bedroom in a study in southern Ontario, Canada (based on 21 cases) ( Table 1) (36). The latest study is from Germany and showed a relative risk of 1.6 (0.7-3.7) for 0.2 µT and 3.2 (1.3-7.8) for nighttime exposure (80).…”
Section: Childhood Cancermentioning
confidence: 99%
“…Other studies in both the United States and Canada did not ®nd associations between wire codes and childhood cancers [including Linet et al, 1997;McBride et al, 1999;Green et al, 1999]. The results from London et al fueled the debate about control selection bias.…”
Section: Introductionmentioning
confidence: 98%